Cancer prognosis and treatment results in patients with PTEN Hamartoma Tumour Syndrome (PHTS)—a European cohort study - Linda A. J. Hendricks; Katja C. J. Verbeek; Janneke H. M. Schuurs-Hoeijmakers; Robin de Putter; Hilde Brems; Sien H. Van Daele; Violetta C. Anastasiadou; Lenka Foretová; Patrick R. Benusiglio; Anna Gerasimenko; Chrystelle Colas; Marie-Charlotte Villy; et al. (BJC Reports)
Abstract Background PTEN hamartoma tumour syndrome (PHTS) patients have a high hereditary risk of cancer, especially breast (BC), endometrial (EC), and thyroid cancer (TC). However, the prognosis of PHTS-related cancers is unknown. Methods This European cohort study included adult PHTS patients with data from medical files, registries, and/or questionnaires. Overall survival (OS) was assessed using Kaplan-Meier analyses and were compared with sporadic cancer and the general population using standardized mortality (SMR) and relative survival rates (RSR). Survival bias was addressed using left-truncation. Results Overall, 147 BC patients were included. The 10y-OS was 77% (95%CI = 66–90), decreasing with increasing stage from 90% (95%CI = 73–100) for stage 0 to 0% (95%CI = 0–0) for stage IV. BC relative survival was comparable to sporadic BC in the first two years (2y-RSR = 1.1; 95%CI = 1.1–1.1) and increasing thereafter (5y-RSR = 1.7; 95%CI = 1.6–1.7). For TC (N = 56) and EC (N = 35), 10y-OS was 87% (95%CI = 74–100) and 64% (95%CI = 38–100), respectively. Overall and cancer-specific mortality in female PHTS patients exceeded general population rates (SMR = 3.7; 95%CI = 2.6–5.0 and SMR = 2.7; 95%CI = 1.6–4.4). Conclusions The prognosis of PHTS-related cancers was comparable to the general population. The higher overall mortality in PHTS patients is presumably related to their higher cancer incidence. These findings, and the high survival observed in early-stage cancer, emphasise the importance of recognising PHTS early to facilitate cancer surveillance.